YIELD OF Asystasia gangetica (L.) subsp. Micrantha FERTILIZED WITH A MIXTURE OF GOAT MANURE AND GRAPE WASTE - N. M. N., Dwiantari,; Witariadi, N. M.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
In an effort to increase livestock productivity, especially ruminants, forage that is available year-round, of good quality, and easy to cultivate is required. One plant that can be utilized as forage is Asystasia gangetica . This study aims to determine the effect of a mixture of goat manure and grape waste on the yield of Asystasia gangetica (L.) subsp. Micrantha. This research was conducted in a greenhouse in Sading Village, Mengwi District, Badung Regency, Bali Province, and lasted for twelve weeks. The design used was a Completely Randomized Design (CRD) consisting of 6 treatments and 5 replications, resulting in 30 experimental units. These treatments included, A: no fertilizer, B: 100% grape waste, C: 100% goat manure, D: 75% goat manure + 25% grape waste, E: 50% goat manure + 50% grape waste, F: 25% goat manure + 75% grape waste. The variables observed were leaf dry weight, stem dry weight, total forage dry weight, leaf dry weight to stem dry weight ratio, and leaf area per pot. The results of the study on Asystasia gangetica (L.) subsp. Micrantha showed that the application of a mixture of goat manure and grape waste in treatment F was not significantly different (P>0.05) from treatments A, B, C, D, and E in terms of leaf dry weight, stem dry weight, total forage dry weight, leaf dry weight to stem dry weight ratio, and leaf area per pot. Based on the research results, it can be concluded that the yield of Asystasia gangetica (L.) subsp. Micrantha was not influenced by the application of a mixture of goat manure and grape waste, and the best mixture of goat manure and grape waste for the yield of Asystasia gangetica (L.) subsp. Micrantha has not been determined.